2022
DOI: 10.1108/jacpr-09-2021-0639
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in incidents during COVID-19 in a Secure Children’s Home: an opportunity for learning

Abstract: Purpose The COVID-19 pandemic is unprecedented for young people within the UK. The pandemic has presented particular challenges for vulnerable children and young people. For example, a recent study in the UK indicated that 83% of young people with existing mental health conditions said the pandemic had made their condition worse (Young Minds, 2020). To date, the impact upon populations such as young people in Secure Children’s Homes (SCHs) is unknown. This study aims to elucidate this area. Design/methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Within the SCH of the current study, findings of a significant decrease in restraints and other incidents including assaults and self-harm were identified six months after the implementation of lockdown measures (McKeown et al , 2022). This is despite increasing incidents such as assaults and self-harm increasing within secure establishments over recent years (HM Government, 2020).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Within the SCH of the current study, findings of a significant decrease in restraints and other incidents including assaults and self-harm were identified six months after the implementation of lockdown measures (McKeown et al , 2022). This is despite increasing incidents such as assaults and self-harm increasing within secure establishments over recent years (HM Government, 2020).…”
Section: Discussionmentioning
confidence: 87%
“…Post COVID-19 lockdown, research within the setting indicated that the number of case formulations for the young people increased, as well as formulation attendees (McKeown et al , 2022). Previous research has indicated that the formulation-led approach promoted by the SECURE STAIRS framework can enhance staff confidence and knowledge regarding the young people that they are working with, particularly when the young person is present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation